Strengthening the National Logistics Network: PT Kereta Api Indonesia's Impact in East Java Province - Rivaldi, Rifki Satya (Universitas Diponegoro, 2024)
Railway transportation plays a pivotal role in Indonesia's economic development, serving as a catalyst for local growth while complementing existing transportation infrastructure. This paper explores the challenges and opportunities within Indonesia's logistics sector, focusing on infrastructure development, system implementation, stakeholder competency, and institutional coordination. Drawing on data from the Ministry of Transportation of Indonesia and the Central Bureau of Statistics (BPS), it highlights the significant impacts of infrastructure on logistics and economic growth, emphasizing the role of railways in driving regional economies. Particularly, the study underscores the cost-effectiveness and efficiency of railways for long-distance product transportation, citing their capacity advantages over trucks. Moreover, it discusses the commercial prospects of rail-based logistics and the complementary relationship between railways and other modes of transportation. By addressing these issues, Indonesia can harness its railway infrastructure to accelerate national economic growth and enhance its position in the global market.